Answers to Dr. Alper Kaliber, University of Birmingham, UK. - Ioannis Mazis (RIEAS, 2007)
A democratic European Turkey, that endorses the acquis communautaire and the European political culture as that has evolved over the last 50 years is not considered by Greece as a security threat. However, certain forms of conduct on the part of our neighbor and NATO ally cause serious concern to Athens and the Greek people, which determines the approach of the Greek government towards Greek-Turkish relations.